120k views
2 votes
Prove that 1÷loga ab + 1÷logb ab=1​

User Oopology
by
5.9k points

1 Answer

5 votes

Answer:

See below.

Explanation:

1 ÷ loga ab + 1 ÷ logb ab

= 1 / (loga ab) + 1 / (loga ab / loga b) { change of log base)

= 1 / (loga ab) + loga b / (loga ab)

= (1 + loga b) / loga ab

= (1 + loga b) / (loga a + loga b) Now loga a = 1 so we have:

((1 + loga b) / (1 + loga b)

= 1.

User Shay Nehmad
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.